Synchronizing the Western Gotland Basin (Baltic Sea) and Lake Kälksjön (central Sweden) sediment records using common cosmogenic radionuclide production variations - Czymzik, Markus; Christl, Marcus; Dellwig, Olaf; Muscheler, Raimund; Müller, Daniela; Kaiser, Jérôme; Schwab, Markus J; Nantke, Carla KM; Brauer, Achim; Arz, Helge Wolfgang (The Holocene, 2024)
Multi-archive studies of climate events and archive-specific response times require synchronous time scales. Aligning common variations in the cosmogenic radionuclide production rate via curve fitting methods provides a tool for the continuous synchronization of natural environmental archives down to decadal precision. Based on this approach, we synchronize 10Be records from Western Gotland Basin (WGB, Baltic Sea) and Lake Kälksjön (KKJ, central Sweden) sediments to the 14C production time series from the IntCal20 calibration curve during the Mid-Holocene period ~6400 to 5200 a BP. Before the synchronization, we assess and reduce non-production variability in the 10Be records by using 10Be/9Be ratios and removing common variability with the TOC record from KKJ sediments based on regression analysis. The synchronizations to the IntCal20 14C production time scale suggest decadal to multi-decadal refinements of the WGB and KKJ chronologies. These refinements reduce the previously centennial chronological uncertainties of both archives to about ± 20 (WGB) and ±40 (KKJ) years. Combining proxy time series from the synchronized archives enables us to interpret a period of ventilation in the deep central Baltic Sea basins from ~6250 to 6000 a BP as possibly caused by inter-annual cooling reducing vertical water temperature gradients allowing deep water formation during exceptionally cold winters.